Resection of Gliomas with and without Neuropsychological Support during Awake Craniotomy—Effects on Surgery and Clinical Outcome - Kelm, Anna; Sollmann, Nico; Ille, Sebastian; Meyer, Bernhard; Ringel, Florian; Krieg, Sandro M. (Frontiers in Oncology, 2017)
Background: During awake craniotomy for tumor resection, a neuropsychologist (NP) is regarded as a highly valuable partner for neurosurgeons. However, some centers do not routinely involve a NP, and data to support the high influence of the NP on the perioperative course of patients are mostly lacking. Objective: The aim of this study was to investigate whether there is a difference in clinical outcomes between patients who underwent awake craniotomy with and without the attendance of a NP. Methods: Our analysis included 61 patients, all operated on for resection of a presumably language-eloquent glioma during an awake procedure. Of these 61 cases, 47 surgeries were done with neuropsychological support (NP group), whereas 14 surgeries were performed without a neuropsychologist (non-NP group) due to a language barrier between the NP and the patient. For these patients, neuropsychological assessment was provided by a bilingual resident. Results: Both groups were highly comparable regarding age, gender, preoperative language function, and tumor grades (glioma WHO grades 1 – 4). Gross total resection (GTR) was achieved more frequently in the NP group (NP vs. non-NP: 61.7% vs. 28.6%, P = 0.04), which also had shorter durations of surgery (NP vs. non-NP: 240.7 ± 45.7 min vs. 286.6 ± 54.8 min, P < 0.01). Furthermore, the rate of unexpected tumor residuals (estimation of the intraoperative extent of resection vs. postoperative imaging) was lower in the NP group (NP vs. non-NP: 19.1% vs. 42.9%, P = 0.09), but no difference was observed in terms of permanent surgery-related language deterioration (NP vs. non-NP: 6.4% vs. 14.3%, P = 0.48). Conclusion: We need professional neuropsychological evaluation during awake craniotomies for removal of presumably language-eloquent gliomas. Although these procedures are routinely carried out with a NP, this is the first study to provide data supporting the NP’s crucial role. Despite the small group size, our study shows statistically significant results, with higher rates of GTR and shorter durations of surgery among patients of the NP group. Moreover, our data emphasizes the common problem of language barriers between the surgical and neuropsychological team and patients requiring awake tumor resection.